THE INTERACTIVE WHITEBOARD IN ENGLISH AS A FOREIGN LANGUAGE (EFL) CLASSROOM - Al-Saleem, Basmah Issa Ahmad (European Scientific Journal, ESJ, 2012)
This study describes and analyses the uses of Interactive WhiteBoards in English as a Foreign Language (EFL) classrooms. It tries to answer the following questions; first, how can an Interactive WhiteBoard be used in a learning environment?, second, how can Interactive WhiteBoards promote student engagement?, and what are Interactive WhiteBoard activities in the EFL classroom?The researcher’s impression is that the interactive whiteboard is a very innovative and powerful support for language acquisition. First of all, it provides a bridge that allows using the features of computers without breaking communication. Secondly, it may enhance new kinds of learning processes. Finally, it offers a very interesting option for bringing the Internet into every EFL class.